PECULIARITIES OF NASAL IRRIGATION IN ACUTE VIRAL RHINOSINUSITIS - Bezshapochniy, S.B.; Loburets, V.V.; Loburets, A.V.; Dzhirov, O.R.; Podovzhniy, O.G. (World of Medicine and Biology, 2020)
The article describes the problems of choosing a solution for the nasal cavity irrigation in acute viral rhinosinusitis. The purpose of the study was to establish the effectiveness of restoring the physiological function of nasal structures by adding to the traditional (3% NaCl solution) saline solution, 6% N-acetylcysteine solution in combination with classical treatment regimen of acute rhinosinusitis. It was found that this combination can effectively restore the mucociliary transport of the nasal mucosa and thus reduce the risk of complications or the migration of the disease into a bacterial form. As a result of the study, we concluded that the combination of N-acetylcysteine with saline solution in the treatment of acute viral rhinosinusitis and improving both the objective and subjective condition of patients.
Keywords: acute viral rhinosinusitis; irrigation; N-acetylcysteine; saline solutions